Literature Study on the Role of Physical Education Philosophy in Character Formation and Student Health - Nurkadri, Nurkadri; Matanari, Vava La Vive; Joy, Joy Immanuel Pakpahan; Alfin, Alfin Siregar (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This article presents a literature review that aims to explore the role of physical education philosophy in shaping character and improving students' health degrees. Physical education is not solely aimed at developing physical aspects, but also contains self-development values that include moral, social, and emotional dimensions. Through a philosophical approach, physical education is seen as a vehicle for the formation of a whole and balanced human being. This study was conducted by examining various scientific sources, such as reference books, journal articles, and relevant research reports. The results of the search show that values such as sportsmanship, discipline, responsibility, and cooperation, are clearly contained in the practice of physical education. These values contribute directly to the formation of students' attitudes and characters. On the other hand, targeted and sustained physical activity also has a positive impact on students' physical fitness and mental health. Thus, it can be concluded that the philosophy of physical education has a strategic role in supporting character formation and improving the quality of life of students. Understanding this philosophical basis is important for educators to have, in order to ensure that the learning process takes place thoroughly and is valuable